Pedagogy and Manipulation in Opinion Columns. An experience from the Critical Epistemic Analysis of Colombian Press Discourse - Vásquez Patiño, Milton (2014)
This paper presents an Epistemic Critical Discourse Analysis matrix applied to the column “Opinion state and clientelism” by Alicia Eugenia Silva, published in newspaper El Tiempo on January 30th 2010 during prelectoral period of campaign to Congress in Colombia. This analisis identifies pedagogical components and didactic strategies in the discourse. Besides, it point out manipulation textual elements that induced to reader for take part for writer’s interests or informative company. Thus, this ignited a complex process between author and reader based on language, ideology, communication of beliefs, and social interaction.